2020
DOI: 10.3390/jcm9061788
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics and Synbiotics on Risk Factors Associated with Cardiometabolic Diseases in Healthy People—A Systematic Review and Meta-Analysis with Meta-Regression of Randomized Controlled Trials

Abstract: We aimed to systematically review the effectiveness of probiotic/synbiotic formulations to counteract cardiometabolic risk (CMR) in healthy people not receiving adjunctive medication. The systematic search (PubMed/MEDLINE/Embase) until 1 August 2019 was performed for randomized controlled trials in >20 adult patients. Random-effect meta-analysis subgroup and meta-regression analysis of co-primary (haemoglobin A1c (HbA1C), glucose, insulin, body weight, waist circumference (WC), body mass index (BMI), choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 117 publications
(197 reference statements)
0
11
0
Order By: Relevance
“…[26][27][28][30][31][32][33]35,36,38,39 Similarly, most of the analyses showed a reduction of other anthropometric measures, including waist circumference, body fat mass, and/or body fat percentage. [26][27][28][29][31][32][33][35][36][37][38] Meta-analyses that included metabolic and inflammation-related parameters predominantly showed beneficial effects for those measures. The improvements were demonstrated for glucose, 28,33,38 HbA1c, 28,33 insulin, 28,33,38 HOMA-IR, 28,33,38 lipids, 28,29,36,38 liver function test, 33 and inflammatory markers.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…[26][27][28][30][31][32][33]35,36,38,39 Similarly, most of the analyses showed a reduction of other anthropometric measures, including waist circumference, body fat mass, and/or body fat percentage. [26][27][28][29][31][32][33][35][36][37][38] Meta-analyses that included metabolic and inflammation-related parameters predominantly showed beneficial effects for those measures. The improvements were demonstrated for glucose, 28,33,38 HbA1c, 28,33 insulin, 28,33,38 HOMA-IR, 28,33,38 lipids, 28,29,36,38 liver function test, 33 and inflammatory markers.…”
Section: Resultsmentioning
confidence: 89%
“…The literature review identified 14 meta-analyses dedicated to evaluating probiotic and/or synbiotic effects on body weight and/or BMI (Table 1). [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Overall, the majority (11 of 14) of meta-analyses showed that probiotic use in RCTs resulted in reduced body weight and/or BMI compared to placebo. [26][27][28][30][31][32][33]35,36,38,39 Similarly, most of the analyses showed a reduction of other anthropometric measures, including waist circumference, body fat mass, and/or body fat percentage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metaanalysis assessing the effect of probiotics on risk factors of cardiometabolic diseases in healthy people revealed reduced BMI and WC and, additionally, total cholesterol (TC) in overweight subjects. Most of the genera were Lactobacillus and Bifidobacterium, the mean time of probiotic administration was 67 days and the daily probiotic dose varied between 10 6 and 10 10 colony-forming units (CFU)/gram [101]. Another meta-analysis confirmed that the improvements in metabolic variables were mostly observed with Bifidobacterium and Lactobacillus genera, adding data on favourable effects of Streptococcus salivarius subsp.…”
Section: Probiotics In Experimental Studiesmentioning
confidence: 91%
“…The meta-analysis assessing the effect of probiotics on risk factors of cardiometabolic diseases in healthy people revealed reduced BMI and WC and, additionally, total cholesterol (TC) in overweight subjects. Most of the genera were Lactobacillus and Bifidobacterium, the mean time of probiotic administration was 67 days and the daily probiotic dose varied between 10 6 and 10 10 colony-forming units (CFU)/gram [ 101 ]. Another meta-analysis confirmed that the improvements in metabolic variables were mostly observed with Bifidobacterium and Lactobacillus genera, adding data on favourable effects of Streptococcus salivarius subsp.…”
Section: Microbiota Interventionsmentioning
confidence: 99%